Bizora: Automated System for Dynamic Pricing and Inventory Management - Muhammad Sohaib; Sonish Aslam; Muhammad Mudassir; Muhammad Owais Nasir; Maryam Tasneem (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Small and medium-sized enterprises (SMEs), particularly those in the restaurant industry, often face challenges with inventory control, pricing strategies, and staff coordination. To address these issues, we have developed an AI-powered SaaS platform that integrates automated inventory management, dynamic pricing, and advanced analytics. The system offers real-time stock monitoring, spoilage tracking, and low stock warnings to reduce waste. It also facilitates order management and the creation of promotions that attract customers. Dynamic pricing algorithms adjust product prices based on factors such as costs, profit margins, and market trends to boost competitiveness. Additionally, AI sales analytics combined with demand forecasting provide valuable business insights, while sentiment analysis and an AI chatbot system ensure exceptional customer interactions and a deeper understanding of customer feedback. The platform also supports sustainability through three Sustainable Development Goals: economic growth (SDG 8), innovation promotion (SDG 9), and responsible consumption and production (SDG 12). By leveraging AI and automation, the platform empowers SMEs to optimize operations, reduce expenses, and make better decisions through streamlined processes